Impact of COVID-19 Pandemic on the Incidence, Prehospital Evaluation, and Presentation of Ischemic Stroke at a Nonurban Comprehensive Stroke Center - Cesar Velasco; Brandon Wattai; Scott Buchle; Alicia Richardson; Varun Padmanaban; Kathy J. Morrison; Raymond Reichwein; Ephraim Church; Scott D. Simon; Kevin M. Cockroft (Stroke Research and Treatment)
Introduction. Many reports have described a decrease in the numbers of patients seeking medical attention for typical emergencies during the COVID-19 pandemic. These reports primarily relate to urban areas with widespread community transmission. The impact of COVID-19 on nonurban areas with minimal community transmission is less well understood. Methods. Using a prospectively maintained prehospital quality improvement database, we reviewed our hospital EMS transports with a diagnosis of stroke from January to April 2019 (baseline) and January to April 2020 (pandemic). We compared the volume of patients, transport/presentation times, severity of presenting symptoms, and final diagnosis. Results. In January, February, March, and April 2019, 10, 11, 17, and 19 patients, respectively, were transported in comparison to 19, 14, 10, and 8 during the same months in 2020. From January through April 2019, there was a 53% increase in transports, compared to a 42% decrease during the same months in 2020, constituting significantly different trend-line slopes (3.30; 95% CI 0.48–6.12 versus -3.70; 95% CI -5.76–-1.64, p=0.001). Patient demographics, comorbidities, and symptom severity were mostly similar over the two time periods, and the number of patients with a final diagnosis of stroke was also similar. However, the median interval from EMS dispatch to ED arrival for patients with a final diagnosis of stroke was significantly longer in January to April 2020 (50±11.7 min) compared to the same time period in 2019 (42±8.2 min, p=0.01). Discussion/Conclusion. Our data indicate a decrease in patient transport volumes and longer intervals to EMS activation for suspected stroke care. These results suggest that even in a nonurban location without widespread community transmission, patients may be delaying or avoiding care for severe illnesses such as stroke. Clinicians and public health officials should not ignore the potential impact of pandemic-like illnesses even in areas of relatively low disease prevalence.